A study of fuzzy data bases: an application to a Peruvian case - Acosta De La Cruz, Pedro R. (2016)
This paper aims to show the various types of data that contain in an intrinsically way fuzzy or imperfect data that are presented in the real world. A form of implementation is described that allows extending the capabilities of a database by using layers levels, emphasizing in the concept of inheritance. What is described is illustrated by an example applied to the Peruvian reality, which is shown with a certain level of detail.